ANALISIS PENGARUH PEMASARAN DIGITAL TERHADAP TINGKAT PENJUALAN PADA TOKO FASHION KOH ACID BANJARBARU - Muhammad Rizali; Riska Desya Safitri (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The purpose of this study is to find out the type of promotion and how much influence digital marketing has as well as the comparison of digital sales with offline sales at fashion stores in Koh Acid Banjarbaru. The object of this research is the Koh Acid Banjarbaru fashion store. The variables used are independent variables, namely digital marketing (X) and dependent variables, namely sales level (Y). The number of samples in this study is 97 consumers of the Koh Acid Banjarbaru store using the incidental sampling method, that is, anyone who happens to meet the researcher can be used as a sample, when viewed by the person who happens to be met as a data source. Secondary data was obtained from the sales report of the Koh Acid Banjarbaru store for the 2024 period for statistical tests and primary data from questionnaires for descriptive analysis. The data analysis techniques are classical assumption tests, simple linear regression, hypothesis tests (t-tests), determination coefficients (R2) and descriptive analysis. The results of the study show that there is an influence of digital marketing on sales rates, this is shown by the regression equation, namely Y = 494,554 + 0.590X If online sales increase by one unit, the overall sales will increase by 0.590. The calculated t value is (2,390) > t table (2,306) and the significant value is 0.044 < 0.05, meaning that the digital marketing variable partially has a positive and significant effect on the sales rate. So it can be concluded that Ho was rejected and Ha was accepted, which means that digital marketing has a positive and significant effect on the sales rate at the Koh Acid Banjarbaru fashion store.